Mechanism of Ru(III) Catalysed Oxidation of Alanine by Ceric Perchlorate in Perchloric Acid Medium - Ram, P.N.; Prasad, Janak (Asian Journal of Chemistry, 2010)
A kinetic investigation of Ru(III) catalysed oxidation of alanine by ceric perchlorate in perchloric acid medium has been made and the results indicate first-order dependence on each of [Ce(IV)], [alanine], [Ru(III)] and [H+]. These kinetic features have led to the conclusion that Ce(IV) first converts Ru(III) to Ru(VIII) quantitatively and Ru(VIII) reacts with protonated alanine to give an intermediate which is attached by Ce(IV) in a slow and rate determining step.